Integrating Polymer-Based Nanoparticles and Green Organic Chemistry for Sustainable Targeted Drug Delivery Systems: A Mechanistic and Environmental Impact Analysis - Dr. Bright Olickal Philip,; Mr. Manish M. Dhanawade,; Mr. Amol A. Pardeshi,; Dr. Saurabh A. Shete,; Dr. Nanabhau B. Karanjule, (The Bioscan, 2026)
The rising need of safer and more efficient systems of drug delivery has inspired a substantial interest in sustainable nanocarriers, especially polymeric nanoparticles that possess improved bioavailability and targeted therapeutic effect (Danhier et al., 2021). Traditional ways of manufacturing nanoparticles generally require the use of toxic solvents and power-demanding chemistry, which also bring doubts to the field of environmental and biological compatibility (Kummerer, 2021). Thus, this research will evaluate the polymer-based nanoparticles that are produced under the green organic chemistry methods of synthesis to enhance targeted delivery of drugs and lower the environmental impact. An experimental research design (primarily) was used, which implied the green synthesis of nanoparticles with the help of biodegradable polymers, including PLGA and chitosan, and physicochemical characterization (dynamic light scattering, electron microscopy, and spectroscopy) (Danaei et al., 2020). Efficiency of drug loading and in vitro release kinetics were evaluated by common analysing techniques, whereas targeting efficiency was measured by cellular uptake performed on the relevant cell lines (Shi et al., 2020). The toxicity and biocompatibility were analysed by MTT assay and oxidative stress indicators, and a life cycle analysis to compare the environmental footprint of the traditional and green synthesis approaches (Zhang et al., 2021). The results indicate that green-synthesized nanoparticles have increased targeting efficiency, longer drug release, as well as, reduced cytotoxicity and environmental impact by a significant level. These findings underscore the possibility of combining green chemistry with nanotechnology in order to come up with efficient, sustainable and clinically translatable drug delivery systems.